Full potential study of the elastic, electronic, and optical properties of spinels MgIn2S4 and CdIn2S4 under pressure effect - F., Semari; R., Khenata; M., Rabah; A., Bouhemadou; S., Omran; Ali H., Reshak; D., Rached (Elsevier Inc., 2011)
Link to publisher's homepage at http://www.elsevier.com/